The book of Isaiah personal impressions of Isaiah Berlin - Hardy, Henry 1949- (The Boydell Press, 2023)
This collection of pen-portraits of the renowned public intellectual Isaiah Berlin, published to mark the centenary of his birth, brings him vividly to life from many vantage points
Previously issued in print: 2009. - Includes index
Keywords: Berlin, Isaiah / 1909-1997; Berlin, Isaiah -- 1909-1997; Aufsatzsammlung